Personality predictors of happiness - Félix Neto (2001)
The Oxford Happiness Inventory and a battery of personality measures were completed by 171 subjects. The results showed predicted positive correlations for happiness with satisfaction with life, Self-esteem, and sociability and negative correlations of happiness with embarrassability, loneliness, shyness, and social anxiety. Four predictors (satisfaction with life, shyness, loneliness, and sociability) accounted for 58% of the variance in happiness scores. These results support previous research as well as validate the Portuguese version of the happiness inventory.